The Effectiveness of Acceptance and Commitment-Based Group Therapy on Hope and Happiness in Women with Breast Cancer - Hedayatian, Negin; Ebrahimi, Mohammad Esmaeil (Applied Family Therapy Journal (AFTJ), 2024)
Objective: This study aimed to examine the effectiveness of acceptance and commitment-based group therapy on hope and happiness in women diagnosed with breast cancer.Methods: The research was applied and experimental in nature. The design was a quasi-experimental pretest-posttest with a control group. The population consisted of all women diagnosed with breast cancer in Borujerd city, from which 30 participants were selected through non-random convenient sampling using Snyder's Hope Scale (1991) and the Oxford Happiness Questionnaire (1990) based on inclusion and exclusion criteria, and were randomly assigned to two groups: the experimental group receiving acceptance and commitment therapy (each group consisting of 15 members) and the control group. The experimental group underwent eight 90-minute sessions of acceptance and commitment therapy, as described by Hayes et al. (2006), once a week, while the control group received no intervention. After the training period, the questionnaires were administered again in both groups at the post-test stage. Data analysis in this study was performed using analysis of covariance.Findings: The results showed that acceptance and commitment-based group therapy significantly improved hope (F = 62.66, p = 0.001) and happiness (F = 43.81, p = 0.001) in women with breast cancer.Conclusion: Based on the findings of this research, it can be concluded that acceptance and commitment-based group therapy enhances hope and happiness in women with breast cancer; therefore, it can be used as an effective intervention method to foster and increase hope and happiness in these women.